Alternative Surgical Treatment Method for 5th Metacarpal Neck Fractures: Comparison of Clinical Outcomes of Intramedullary and Transverse K-Wire Fixations with Additional Antirotational K-Wire - Kasman, U. O; Turemis, C; Surucu, S; Korkmaz, Ö (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: The purpose of this study was to assess the clinical outcomes and complications associated with intramedullary and transverse K-wire fixations of 5th metacarpal neck fractures. MATERIAL AND METHODS: Patients who were operated for 5th metacarpal neck fractures between 2019 and 2022 were evaluated retrospectively. Regarding the surgical treatment methods, patients were assessed by dividing them into two groups. The first group comprised patients who underwent treatment with an intramedullary K-wire. The second group comprises patients who underwent transverse K-wire fixation. RESULTS: The average quick DASH score of all patients was 5.6±4.7 in the intramedullary K-wire fixation group and 5.9±5.1 in the transverse K-wire fixation group. An average 5th finger metacarpophalangeal joint extension limitation was 6.2±5.7° in the intramedullary fixation group and 6.1±5.8° in the transverse K-wire group. The mean radiological union time was 4.9±0.7 weeks in the intramedullary fixation group and 5.1±0.7 weeks in the transverse K-wire group. No statistically significant difference was found between the quick DASH scores and degrees of the MCP joint extension limitation ( p=0.785). Intramedullary fixation and transverse K-wire fixations are effective surgical treatment methods for metacarpal neck fractures. DISCUSSION: It has been reported that the intramedullary fixation method in metacarpal bone fractures is more effective than the fixation methods with cross and transverse K-wire. But our results revealed no difference in clinical outcomes between the two surgical fixation methods. CONCLUSIONS: We observed no statistically significant difference between the two fixation techniques with regard to union, clinical outcomes, or complications. KEY WORDS: intramedullary fixation; metacarpal neck fracture; transverse K-wire fixation.
Keywords: Metacarpal Bones; dospělí; fraktury kostí; Female; intramedulární fixace fraktury; Adult; výsledek terapie; ženské pohlaví; metakarpální kosti; lidé; Fractures, Bone; Treatment Outcome; Middle Aged; Fracture Fixation, Intramedullary; retrospektivní studie; Male; vnitřní fixace fraktury; lidé středního věku; kostní dráty; mužské pohlaví; Retrospective Studies; Bone Wires; Fracture Fixation, Internal; Humans